Interpreting in the Community and Workplace - Rudvin, Mette. author. aut Link
X, 237 p.
Keywords: An innovative and comprehensive guide that can be applied to a wide range of dialogue settings this educational tool for trainers in all fields of dialogue interpreting addresses not only the two key areas of Community- and Public Service Interpreting, the legal and health sectors, but also business interpreting.